Photometric determination of asteroid 9 Metis rotation period using the OZT-ALTS robotic telescope - Achmad Zainur Rozzykin; Aditya Abdilah Yusuf; Ridlo Wahyudi Wibowo; Adhitya Oktaviandra; Novia Doloyanty Br Sinaga; Zeni Septiani; Muhammad Rafiansyah; Ioga Lazuardi (Fakultas Sains Institut Teknologi Sumatera, 2025)
Asteroid 9 Metis, a prominent main-belt object with an irregular shape and diameter of approximately 190 km, provides insights into early solar system formation and evolution. We determined its synodic rotation period through ground-based photometric observations using the OZT-ALTS robotic telescope at Institut Teknologi Sumatera (Itera). Observations were conducted on May 6, 2025, spanning 6.2 hours continuously. We analyzed 125 calibrated light frames using aperture photometry to construct a light curve. Period analysis employed the Lomb-Scargle periodogram method, suitable for unevenly spaced astronomical data. The periodogram revealed a dominant peak at 2.51 hours. However, the folded light curve exhibited characteristic double-peaked structure with two maxima and minima per cycle, indicating this represents half the actual rotation period. The true synodic rotation period was therefore determined as 5.01 ± 1.01 hours. This result agrees with previously reported values ( 5.08 hours), confirming that asteroid 9 Metis has an elongated shape or heterogeneous surface reflectivity. Our study demonstrates that accurate rotational periods can be obtained using moderate-sized telescopes and modern photometric techniques for kilometer-scale asteroids. These findings contribute to understanding asteroid rotational dynamics and provide reference data for future shape modeling studies.